Disability index: a measure of deprivation among disabled - Mishra, A.K.; Gupta, Ruchika (2006)
A disability index of education, skill development and employment, based on National Sample Survey and Census 2001 data presents a gloomy picture of the life of the disabled in India. It shows the limitation of various rehabilitation measures adopted by the government and non-governmental organisations. There is also an unawareness of some of the facilities that are available. - Reproduced.
Keywords: Disabilities